Nursing pharmacology made incredibly easy - Scott, William N.; McGrath, Deirdre (Philadelphia, Pennsylvania : Wolters Kluwer/Lippincott Williams & Wilkins, 2009)
Explains difficult and complex pharmacology concepts. This text covers fundamentals of pharmacology, including where drugs come from, how they are classified and administered, drugs by pharmacologic class for all body systems, as well as pain medications, and potentially dangerous drug interactions
1. Fundamental of nursing pharmacology -- 2. Autonomic nervous system drugs -- 3. Neurologic and neuromuscular drugs -- 4. Pain medication -- 5. Cardiovascular drugs -- 6. Respiratory drugs -- 7. Gastrointestinal drugs -- 8. Haematologic drugs -- 9. Endocrine drugs -- 10. Psychotropic drugs -- 11. Anti-infective drugs -- 12. Anti-inflammatory and immunomodulating drugs -- 13. Antineoplastic drugs
Includes index
Keywords: Nursing; Pharmacology